The therapeutic relationship and adherence to antipsychotic medication in schizophrenia - McCabe, Rosemarie; Salize, Hans Joachim (PLOS ONE, 2012)
Objective Previous research has shown that a better therapeutic relationship (TR) predicts more positive attitudes towards antipsychotic medication, but did not address whether it is also linked with actual adherence. This study investigated whether the TR is associated with adherence to antipsychotics in patients with schizophrenia. Methods 134 clinicians and 507 of their patients with schizophrenia or a related psychotic disorder participated in a European multi-centre study. A logistic regression model examined how the TR as rated by patients and by clinicians is associated with medication adherence, adjusting for clinician clustering and symptom severity. Results Patient and clinician ratings of the TR were weakly inter-correlated (rs = 0.13, p = 0.004), but each was independently linked with better adherence. After adjusting for patient rated TR and symptom severity, each unit increase in clinician rated TR was associated with an increase of the odds ratio of good compliance by 65.9% (95% CI: 34.6% to 104.5%). After adjusting for clinician rated TR and symptom severity, for each unit increase in patient rated TR the odds ratio of good compliance was increased by 20.8% (95% CI: 4.4% to 39.8%). Conclusions A better TR is associated with better adherence to medication among patients with schizophrenia. Patients' and clinicians' perspectives of the TR are both important, but may reflect distinct aspects.
Gesehen am 24.04.2018